2019
DOI: 10.1016/j.jjcc.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignancy in heart transplant recipients: A single center experience in Japan

Abstract: Heart transplantation (HTx) is an established and effective treatment for advanced heart failure [1]. The long-term prognosis after HTx has continuously improved as a consequence of reduced early post-transplant mortality [2]. In Japan, the survival rates at 5, 10, and 15 years after HTx are 92.7%, 89.6%, and 81.8%, better than those in Europe and the USA [3]. However, the incidence of de novo malignancy increases in the late period and is one of the major causes of death after HTx [4]. Malignancy negatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some de novo malignancies following surgery have been reported. Kimura et al 6 reported an increase in the overall incidence of de novo malignancies after heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Some de novo malignancies following surgery have been reported. Kimura et al 6 reported an increase in the overall incidence of de novo malignancies after heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the series focusing on the post-transplant malignancy, PTM had no significant effect, although the hazard ratio was just over 1.5 [16]. Some series had very low numbers [1,9,14]. Therefore, the results of small series warrant caution.…”
Section: Recurrences Of Neoplasms and Causes Of Deathmentioning
confidence: 94%
“…One series showed that hazard ratio of PTM on post-transplant malignancy was 1.5, but this was not significant [16]. Another series showed a significant difference in this respect (1/96 v. 1/14) but the absolute numbers were very low and other factors such as the type of induction treatment should be accounted for [14]. Interestingly, one series showed that skin cancer was by far the most common post-transplant malignancy, followed by lung cancer, prostate cancer and PTLD.…”
Section: Post-transplant Neoplasmsmentioning
confidence: 95%
See 2 more Smart Citations